Consider developing a college athletics review board to enhance transparency. Issue 11 (February 2016) - Neal, Timothy; O'Brien, Timothy
Abstract : The recent release of the movie Concussion has generated significant interest in and sensitivity about the medical treatment of athletes at all levels.